Guarantee in Islamic Law Perspectives: A Theoretical discussion of Fiqh Al-Muqārin/Madhāhib Comparison - Muhajirin Muhajirin (UIN Sunan Gunung Djati Bandung, 2018)
Guarantee in Islamic Law Perspectives: Guarantee is a system that usually comes in the selling of automotive or electronics product, including others. The reason for this guarantee application for producer is basically to increase the selling rate of one product. While for the consumers this is a form of protection to the item they have purchased. There is indeed a mutualism relationship in this practice. The discussion of the application of guarantee in an Islam Law of trade practice is still being argued whether it is legal or not among the scholars. This happens because of the differences of foundation they use in establishing the legality of guarantee in Islam trade. The definition of guarantee in Indonesia state Law can be found in verse 1316 of Law Book, which is: guarantee is an enclose later from a product saying that the producers ensure a particular product from any worker mistakes and material failure during certain time. The result of this research is the enclosing of Guarantee given in trade as a promise between seller and buyer to ensure the satisfaction of the buyer. The consequence would be to replace the item by justifying its damage.